Modeling sustainability visions: A case study of multi-scale food systems in Southwestern Ontario. (1st February 2019) - Halbe, Johannes; Adamowski, Jan
Abstract: The process of systematically developing a sustainability vision is an important element of effective environmental management. Sustainability visions can, however, include contradictions and counterintuitive effects due to complex system behavior (e.g., feedback loops, multi-causality) and ambiguous system boundaries (e.g., choice of a scale, such as a regional or national scale). This paper proposes an innovative methodological framework for vision design and assessment (VDA) to analyze the sustainability of future visions on multiple scales with consideration of ecosystem services, and to test their plausibility based upon expert and local knowledge. First, requirements and functions of visionary system designs are identified. Second, a functional organizational analysis defines structures and processes that generate functions. Third, a literature review and participatory modeling process are conducted to analyze the system structures of visionary system designs using causal loop diagrams. Fourth, fuzzy cognitive mapping is used to assess visions based upon sustainability indicators. A case study on sustainable food systems in Southwestern Ontario, Canada, is provided to demonstrate the application of the methodology. Three designs of a sustainable food system were analyzed and tested: urban organic gardening, a local diversified organic food system and a globalized commodity-based organic food system. The results show the advantages and disadvantages of each system design and underline the sustainability benefits of a multi-scale food system based upon a combination of system designs. Highlights: Coherent sustainability visions are critical for effective environmental management. We propose a framework to design and assess sustainability visions. The framework uses functional analysis, conceptual modeling, fuzzy cognitive maps. A case study in Ontario on sustainable food systems is provided. The results show various sustainability benefits of a multi-scale food system.